2018
DOI: 10.3390/cancers10090309
|View full text |Cite
|
Sign up to set email alerts
|

A Dietary Intervention to Lower Serum Levels of IGF-I in BRCA Mutation Carriers

Abstract: Background: Insulin-like growth factor I (IGF-I) and other markers of insulin resistance (IRm) might influence the penetrance of BRCA gene mutation. In a demonstration project on BRCA mutation carriers we tested the effect of the ‘Mediterranean diet’, with moderate protein restriction, on serum levels of IGF-I and IRm. Methods: BRCA mutation carriers, with or without breast cancer, aged 18–70 years and without metastases were eligible. After the baseline examinations, women were randomized to an active dietary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 43 publications
1
14
0
4
Order By: Relevance
“…Women often inquire about less invasive risk-reducing options, including dietary and physical activity recommendations, and physicians need to be able to give them evidence-based answers regarding their lifestyle choices, especially for those who opt not to undergo surgery or chemoprevention. The present results and our previous findings [ 10 , 11 , 13 ] indicate that women carriers, if properly instructed, are capable of substantially improving their dietary habits, with significant reduction in their potential modulators of BRCA penetrance. In Germany, the LIBRE study has concluded its feasibility phase (LIBRE-1) confirming the practicability of an intervention involving Mediterranean diet and physical activity in BRCA mutation carriers [ 22 , 23 ].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Women often inquire about less invasive risk-reducing options, including dietary and physical activity recommendations, and physicians need to be able to give them evidence-based answers regarding their lifestyle choices, especially for those who opt not to undergo surgery or chemoprevention. The present results and our previous findings [ 10 , 11 , 13 ] indicate that women carriers, if properly instructed, are capable of substantially improving their dietary habits, with significant reduction in their potential modulators of BRCA penetrance. In Germany, the LIBRE study has concluded its feasibility phase (LIBRE-1) confirming the practicability of an intervention involving Mediterranean diet and physical activity in BRCA mutation carriers [ 22 , 23 ].…”
Section: Discussionsupporting
confidence: 82%
“…We conducted a randomized controlled trial [ 10 , 11 , 12 , 13 , 14 ] of women with deleterious BRCA1 / 2 mutations to test whether a Mediterranean dietary intervention with moderate protein restriction significantly reduces IGF-I and other potential modulators of penetrance.…”
Section: Introductionmentioning
confidence: 99%
“…There was a statistically significant difference between the basal blood glucose and insulin levels at T0 and at T2 ( p = 0.0405 and p < 0.0001 respectively); this is in accordance with the literature: Pasanisi et al conducted a randomized controlled trial evaluating the adhesion to MD and the IGF-1 levels and other markers of insulin resistance in BRCA mutation carriers. In the trial, 203 patients were randomized and those in the experimental arm showed a reduction in IGF-1 levels [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Study design and patients. The multicenter dietary intervention trial on BRCA-mutant women has been described elsewhere (30,31). Briefly, that study investigated whether an active dietary intervention based on the 'Mediterranean diet' with moderate protein restriction -mainly milk and animal protein, down to 10-12% of total calorie intake -and recommendations for physical activity significantly reduced IGF-I and other markers of insulin resistance.…”
Section: Methodsmentioning
confidence: 99%
“…In a sample of BRCA-mutant women in a dietary intervention trial to reduce serum levels of IGF-I and other markers of insulin resistance (30,31), we explored the role of the baseline serum levels of adiponectin and leptin and their relation with the SNP276G>T as possible modulators of BRCA penetrance.…”
mentioning
confidence: 99%